PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yan Christin Br. Sembiring (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
The purpose of this study is empirically examine the effects of institutional ownership and managerial ownership on financial performance in banking companies listed on the Indonesian Stock Exchange during 2016-2017 consisting of 43 companies. The method used in this research is purposive sampling method where companies that meet the criteria amount to 20 companies, so that get 40 companies as analysis unit. The analysis shows that the data used in this study meet the classic assumption test. The result of Multiple Linear Regression Analysis shows that institutional ownership has no significant effect on financial performance, but managerial ownership has positive significant effect on financial performance. Two varibles have no significant effect on financial performance simultaneously.